Erigena’s Conception of the Sacraments - Walker, G. S. M. (Studies in church history, 1966)
This footnote to the eucharistic debate of the ninth century is perhaps worth attempting for two reasons. In the first place, Erigena the philosopher occupies a highly individual stand-point. As a layman, nullis ecclesiasticæ dignitatis gradibus insignitum, he avoided the influence of the Gallican liturgical tradition in which, as nowhere else at the time, Christ’s real presence was stressed together with an actual change in the consecrated elements. In the second place, the only adequate account of his ideas is that provided by Geiselmann; and even this suffers from a failure to apprehend the full significance of the philosophical background to Erigena’s thought.